KONSUMSI LEMAK, STATUS GIZI PADA USIA MENARCHE 01 SEKOLAH DASAR 01 SDN KERTAJAYA SURABAYA - Nursarita Intan; Irine Christiany (JURNAL PENELITIAN KESEHATAN, 2015)
Menarche is a sign In which a young woman who grew up Influenced by several factors, one of whichis nutrition. This study alms to determine the correlation between fat Intake and nutritional status. and age of menarche In elementary school. This study used a cross-sectional study design with asample of 15 female students. Research subjects were interviewed with the SQ-FFQ and Remember2x24hours and had anthropometric (height and weight) were measured.Data were analyzed by Spearman test with a = 0.05. The results showed that 80% of respondentsaged 11 years and 73.3% of respondents experienced a precocious menarche. fat consumption from53.3% of respondents were excessive. WeIght growth Indicator based on student respondents BMI/ Age was obese (SO 1.07). The high growth seen with Indicator High / normal Age (SO 0.24).From bivariate analYSis using Spearman correlation statIstical test showed that there Is a relationshipbetween fat consumption at the age of menarche in 5th grade female students of SON KertajayaSurabaya who had menarche, It shows In the data analysiS with p value of O.009 (p 0. OS) and therewas a relationship between nutritional status and age at menarche in 5th grade student of SONKertajaya Surabaya who had menarche, revealed by data analysiS with p value of 0.001 (p 0.05).Keywords: menarche, nutritional status, level of fat consumption, age of menarche